A new strategy for hydrophobic drug delivery using a hydrophilic polymer equipped with stacking units. Issue 59 (9th July 2018) - Cui, Peng-Fei; Zhuang, Wan-Ru; Hu, Xi; Xing, Lei; Yu, Ru-Yi; Qiao, Jian-Bin; He, Yu-Jing; Li, Fangyuan; Ling, Daishun; Jiang, Hu-Lin
Abstract : A highly hydrophilic polymer was used to deliver aromatic ring-containing hydrophobic agent doxorubicin (DOX) via π–π interaction. Abstract : A highly hydrophilic polymer equipped with guanidinium groups was used to load aromatic ring-containing hydrophobic agent doxorubicin (DOX) via π–π interaction. The results have shown that the delivery system exhibited enhanced cellular uptake and antitumor efficiency compared with free drugs. This study opens new avenues for the application of hydrophilic polymers in drug delivery.